New technology, new approaches: Collaborative and interdisciplinary teaching on violence against women - Sandell, Karen S (2003)
The use of distance learning technology provides educators with creative and innovative opportunities to reach a variety of students in different fields of study. This article describes the collaborative development of an interdisciplinary distance learning course focusing on research, theory, and practice in the area of violence against women. Course development considerations, issues, outcomes, and recommendations for the use of specific technologies are discussed